2023
DOI: 10.3390/v15030656
|View full text |Cite
|
Sign up to set email alerts
|

Virological Markers in Epstein–Barr Virus-Associated Diseases

Abstract: Epstein–Barr virus (EBV) is an oncogenic virus infecting more than 95% of the world’s population. After primary infection—responsible for infectious mononucleosis in young adults—the virus persists lifelong in the infected host, especially in memory B cells. Viral persistence is usually without clinical consequences, although it can lead to EBV-associated cancers such as lymphoma or carcinoma. Recent reports also suggest a link between EBV infection and multiple sclerosis. In the absence of vaccines, research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 172 publications
0
1
0
Order By: Relevance
“…This virus exhibits two primary modes of infection: a latent state of infection and active viremia, the latter being attributed to the lytic potential of the virus (17). Infection with this oncogenic virus may remain asymptomatic in a certain number of individuals (18). Some studies that have been carried out so far have shown that the percentage of viruses in Reed-Sternberg cells that are pathognomonic for Hodgkin's lymphoma, and that possessed a given virus, ranges up to over 70%.…”
Section: Infectionmentioning
confidence: 99%
“…This virus exhibits two primary modes of infection: a latent state of infection and active viremia, the latter being attributed to the lytic potential of the virus (17). Infection with this oncogenic virus may remain asymptomatic in a certain number of individuals (18). Some studies that have been carried out so far have shown that the percentage of viruses in Reed-Sternberg cells that are pathognomonic for Hodgkin's lymphoma, and that possessed a given virus, ranges up to over 70%.…”
Section: Infectionmentioning
confidence: 99%
“…(5) The reactivation of latent viruses, such as EBV, VZV, HSV and HHV-6, during and after acute COVID-19 infection in various organs may lead to a plethora of chronic symptoms after COVID-19 (e.g., fatigue, myalgia, cognitive disorders) [ 103 ]. These viruses have been implicated in several disorders, including rheumatoid arthritis, multiple sclerosis, lymphomas and cancers [ 104 , 105 , 106 , 107 , 108 , 109 ].…”
Section: Pathogenesis Of Long Covidmentioning
confidence: 99%